Analysis of the Influence of Brand and Halal Label on Skincare Product Purchase Decisions with Price as a Moderating Variable - Rahmatika, Lora; Saragi, Sahat; Amyulianthy, Rafrini (GoAcademica Research & Publishing, 2025)
In 2018, the cosmetic industry saw a 20% increase in growth compared to the previous year, reflecting a rise in market share. Notably, out of Indonesia’s population of 231.06 million, approximately 86.7% are Muslims. Since 2010, Wardah has emerged as the first pioneer of halal cosmetics in Indonesia, followed by several other brands, contributing significantly to the industry's continued growth. Key features that attract the Muslim market include halal attributes, such as halal certification labels. When making purchasing decisions, consumers tend to consider various factors, including brand reputation, brand image, label information, and price. This study aims to examine the influence of brand and halal labeling on consumers' purchase decisions for skincare cosmetics, with price serving as a moderating variable. Data were collected using a Likert-scale questionnaire completed by 136 respondents. The data were analyzed using SEM PLS version 4. The findings reveal that both brand and halal labeling significantly affect purchase satisfaction, with path coefficient values of 0.187 and 0.509, respectively. Additionally, price was found to moderate these relationships: it weakens the influence of brand on purchase decisions (path coefficient = -0.180) but strengthens the impact of halal labeling (path coefficient = 0.226). In conclusion, this study demonstrates that brand and halal labeling both play crucial roles in shaping consumer purchasing decisions. Furthermore, pricing acts as a moderating factor—diminishing the brand's effect while amplifying the impact of halal labeling on purchase behavior.